2020
DOI: 10.18632/aging.102698
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 inhibits growth and metastasis of hepatocellular carcinoma cells via Wnt/β-catenin pathway

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer worldwide, and it is the second leading cause of cancer-related mortality. Aquaporin 9 (AQP9) is an essential aquaporin in the liver and located in the basolateral membrane of hepatocytes, but its roles on HCC has not been completely elucidated. This study investigated the regulatory functions of AQP9 in the pathogenesis of HCC. The expression levels of AQP9 were significantly down-regulated in HCC tissues and cells, which was also correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
(37 reference statements)
0
36
0
Order By: Relevance
“…It is crucial for the maintenance of the stemness of murine mesenchymal stem cells [ 24 , 25 ]. AQP9 is downregulated in hepatocellular carcinoma but is elevated in many other cancers, including clear cell renal cell carcinoma, which suggests that it plays a complex role in cancer development [ 26 , 27 ]. A few bioinformatic studies have shown that COL8A1 is a hub gene associated with several cancers, but this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial for the maintenance of the stemness of murine mesenchymal stem cells [ 24 , 25 ]. AQP9 is downregulated in hepatocellular carcinoma but is elevated in many other cancers, including clear cell renal cell carcinoma, which suggests that it plays a complex role in cancer development [ 26 , 27 ]. A few bioinformatic studies have shown that COL8A1 is a hub gene associated with several cancers, but this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that PCNA knockdown-HepG2 cells under hypoxia showed the induction of more epithelial-mesenchymal transition (EMT) process compared to the control [19]. PCNA and EMT-related markers were down-regulated following treatment with Wnt/β-catenin signaling inhibitor (XAV939) and the proliferative activity of HCC cells was significantly inhibited [20]. MutS homolog 6 (MSH6) is a member of the DNA mismatch repair MutS family.…”
Section: Discussionmentioning
confidence: 99%
“…AQP9 acts as a tumor suppressor in HCC invasion via the regulation of HIF-1α expression in the tumor hypoxic microenvironment. Furthermore, AQP9 overexpression was found to result in reactive oxygen species (ROS) accumulation, which inhibited β-catenin activity by attenuating the interaction of β-catenin with TCF4 while concurrently enhancing the association of β-catenin with FOXO3a, ultimately inhibiting liver cancer stem cells (LCSCs) (12,(14)(15)(16)(17); However, the prognostic value of AQP9 and the specific mechanism underlying its role in HCC remain to be further elucidated. Therefore, in this study, we conducted a bioinformatics analysis of AQP9 in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liver steatosis is characterized by ectopic accumulation of fat and altered glycerol uptake, and interestingly, AQP9 are dysregulated in liver steatosis mice (11)(12)(13). In humans, there is evidence to suggest that AQP9 inhibits the progression of HCC via the Wnt/β-catenin pathway (14), as well as epithelialto-mesenchymal transition (15) and the ROS-HIF-1α signaling pathway (16,17). However, the value of AQP9 in the diagnosis and prognosis of HCC as well as the changes in genes and pathways related to AQP9, immune infiltration levels and the reason for the decrease of AQP9 expression in HCC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%